Adjuvant activity of tubeimosides by mediating the local immune microenvironment - Han, Ziyi; Jin, Junjie; Chen, Xiangfeng; He, Yanfei; Sun, Hongxiang (Frontiers in Immunology, 2023)
Rhizoma Bolbostemmatis, the dry tuber of Bolbostemma paniculatum, has being used for the treatment of acute mastitis and tumors in traditional Chinese medicine. In this study, tubeimoside (TBM) I, II, and III from this drug were investigated for the adjuvant activities, structure-activity relationships (SAR), and mechanisms of action. Three TBMs significantly boosted the anti-gen-specific humoral and cellular immune responses and elicited both Th1/Th2 and Tc1/Tc2 re-sponses towards OVA in mice. TBM I also remarkably facilitated mRNA and protein expression of various chemokines and cytokines in the local muscle tissues. Flow cytometry revealed that TBM I promoted the recruitment and antigen uptake of immune cells in the injected muscles, and aug-mented the migration and antigen transport of immune cells to the draining lymph nodes. Gene expression microarray analysis manifested that TBM I modulated immune, chemotaxis, and in-flammation-related genes. The integrated analysis of network pharmacology, transcriptomics, and molecular docking predicted that TBM I exerted adjuvant activity by interaction with SYK and LYN. Further investigation verified that SYK-STAT3 signaling axis was involved in the TBM I-induced inflammatory response in the C2C12 cells. Our results for the first time demonstrated that TBMs might be promising vaccine adjuvant candidates and exert the adjuvant activity through mediating the local immune microenvironment. SAR information contributes to developing the semisynthetic saponin derivatives with adjuvant activities.